Questions and Answers : a Guide to Fitness and Wellness - LIGUORI, Gary, Sandra Carroll-Cobb (2014)
Have you ever wondered : How can I reduce my body fat? Are there ways I can lower the stree in my life? When is the best time of day to work out? How many days a week should I work out?